Kajian Sistem Klasifikasi Keamanan dan Akses Arsip di Depo Arsip Kabupaten Bandung - Chandra, Devita; Sukaesih, Sukaesih (Ilmu Informasi Perpustakaan dan Kearsipan, 2023)
Archive management is supported by four pillars which will determine the effectivity and efficiency of archival managing work. The pillars consist of Official Script Layout, Archives Classification Codes, Archives Retention Schedules, and Archives Access and Security Classification Systems. This paper mainly discussed one of the pillars that supported archive management activity which was Archives Access and Security Classification Systems. This research was conducted by means of descriptive qualitative methods, which aimed for gaining clarity in regards of the subject of study. As the role model of other archival institutions or work units, ANRI issued a regulation regarding Archives Access and Security Classification Systems to maintain security, confidentiality, and physical form of archives. Result shows that Archives Access and Security Classification Systems issued by the district government of Bandung Regency has covered the means of protecting the confidentiality of archives. The regulation, specifically Regent Regulations Number 130 Year 2018, covered these following aspects; archive classification, access classification, means and infrastructure, along with various types of users. This paper will also include sets of examples published within the official regulation to ensure that the information given is clear and detailed.